(Con)figuring gender in Bible translation: Cultural, translational and gender critical intersections - Punt, J. (HTS teologiese studies, 2014)
The gendered intersection of cultural studies and Bible translation is under acknowledged. Accounting for gender criticism in translation work requires, besides responsible theory and practice of translation, also attention to interwoven gender critical aspects. After a brief investigation of the intersections between biblical, translation and gender studies, translation in a few Pauline texts with bearing on gender and sexuality are investigated.